PENGARUH KOMUNIKASI INTERPERSONAL GURU DAN SISWA TERHADAP MOTIVASI BELAJAR PADA SMPN TERBUKA 9 KOTA PEKANBARU - Nur ‘Amalaia; Anuar Rasyid (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Communication is the key to the success of integrating in the teaching and learning process, the motivational aspect largely determines the intensity of the learning effort and encourages students to carry out certain activities related to learning activities. Motivation is also one of the factors that will later influence achievement. Optimal learning outcomes are influenced by various components of teaching and learning, including effective interpersonal communication by the teacher. So that interpersonal communication skills possessed by the teacher are able to influence students in the form of motivation and enthusiasm in following the learning process and supporting learning success. This study aims to determine the effect of teacher interpersonal communication on student motivation at open junior high school 9 in Pekanbaru city.The method used in this research is quantitative method. Data collection techniques using questionnaires and documentation. The population in this study were students of grades VIII and IX open junior high school 9 in Pekanbaru city. The sampling technique used is a census of respondents. To determine the effect of these two variables, researchers used simple linear regression analysis. And for the processing of the questionnaire test data is carried out by using the version 24 of the Windows Product and Service Solution (SPSS) Statistics program. Based on the results of simple linear regression in this study, the regression coefficient value is Y = 2.11 + 0.682 X with a significance level of 0.00 and smaller than α = 0.05. While based on the determination test, the results obtained were 32.4%. This means that there is a weak influence between interpersonal communication of teachers on learning motivation of students at open junior high school 9 in Pekanbaru city.